2007
DOI: 10.1021/ja075750o
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Highly Regio- and Stereoselective Conjugate Addition of 2,3-Allenoates with Grignard Reagents

Abstract: An efficient highly regio- and stereoselective iron-catalyzed conjugate addition of 2,3-allenoates with primary or secondary alkyl, phenyl, or vinyl Grignard reagents to synthesize multi-substituted beta,gamma-unsaturated enoates has been reported. The in situ formed magnesium dienolate may readily react with different electrophilic reagents to construct an allylic quaternary carbon at the alpha-position of the ester group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Ma and co-workers described the Fe(acac) 3 -catalyzed carbometalation of 2,3-allenoates which after hydrolysis afforded β,γ-unsaturated esters under very mild conditions (Scheme 388). 687 The reaction proceeded with high regio-and stereoselectivity and provided the trisubstituted olefins in high yields. The feasibility of trapping the intermediate magnesium dienolate with other electrophiles was proven by reaction with acrolein, acetyl chloride, and methyl chloroformate.…”
Section: Carbometalationmentioning
confidence: 98%
“…Ma and co-workers described the Fe(acac) 3 -catalyzed carbometalation of 2,3-allenoates which after hydrolysis afforded β,γ-unsaturated esters under very mild conditions (Scheme 388). 687 The reaction proceeded with high regio-and stereoselectivity and provided the trisubstituted olefins in high yields. The feasibility of trapping the intermediate magnesium dienolate with other electrophiles was proven by reaction with acrolein, acetyl chloride, and methyl chloroformate.…”
Section: Carbometalationmentioning
confidence: 98%
“…For example, Michael addition or alkylation of the ring-opened products was accomplished efficiently without compromising the integrity of the alkene [Eq. (6) and Eq. (7)].…”
Section: Methodsmentioning
confidence: 99%
“…This process leads to b,g-unsaturated ester building blocks, which can be difficult to prepare using alternative methods owing to possible migration of the alkene into conjugation. [6] Owing to their highly strained nature, cyclopropenes exhibit a diverse range of reactivities, which present unique opportunities for organic synthesis. [7] Although cyclopropenes are susceptible to a range of useful carbometalation (and hydrometalation) reactions, [7,8] a significant majority of examples described to date result in preservation of the threemembered ring to provide highly functionalized cyclopro-panes (Scheme 1, left).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ma reported that treatment of a 2,3-allenoate with methylmagnesium reagent in the presence of a catalytic amount of iron catalyst exclusively gave the corresponding product 5e (Scheme 47) [134]. Not only primary alkylmagnesium reagents but also secondary alkyl-, phenyl-, and vinylmagnesium reagents could be employed.…”
Section: Reviewmentioning
confidence: 99%